Policy Adherence And Business Growth: Exploring The Relationship In Small And Medium Enterprises - AKANG, AKANINYENE UDO (MNIM) (Zien Journals, 2024)
Small and Medium Enterprises (SMEs) play a vital role in economic growth worldwide but often face challenges in adhering to policies. This study investigates the relationship between policy adherence and business growth in SMEs. The study explores how policy adherence influences various aspects of SME operations and their growth trajectory through mixed-method research, including surveys and interviews with SME representatives. Descriptive analysis reveals a strong correlation between policy adherence and business growth, supported by significant statistical findings. The study confirms that SMEs operating within supportive regulatory frameworks are better equipped to withstand external shocks, create job opportunities, and enhance social welfare. Policymakers are urged to develop tailored support mechanisms, including accessible resources and simplified regulatory processes, to assist SMEs in navigating complex policy landscapes effectively. By fostering an enabling environment for SMEs, policymakers can promote inclusive and sustainable economic growth, ensuring prosperity and resilience at both local and global levels.
Keywords: Policy adherence; Business growth; small and medium enterprises